2023
DOI: 10.3389/fmicb.2023.1109881
|View full text |Cite
|
Sign up to set email alerts
|

Infection dynamics, transmission, and evolution after an outbreak of porcine reproductive and respiratory syndrome virus

Abstract: The present study was aimed at describing the infection dynamics, transmission, and evolution of porcine reproductive and respiratory syndrome virus (PRRSV) after an outbreak in a 300-sow farrow-to-wean farm that was implementing a vaccination program. Three subsequent batches of piglets (9–11 litters/batch) were followed 1.5 (Batch 1), 8 (Batch 2), and 12 months after (Batch 3) from birth to 9 weeks of age. The RT-qPCR analysis showed that shortly after the outbreak (Batch 1), one third of sows were deliverin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 79 publications
1
8
1
Order By: Relevance
“…One crucial pillar of disease control is the genetic characterization of circulating virus strains in order to identify the origin of infection and determine the routes of transmission between pig farms, within a geographical region or an administrative area. Sequencing one of the most variable genomic regions, the ORF5, is still a gold-standard procedure for surveying these issues [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. The information obtained by means of molecular epidemiology further assists the improvement of external disease control measures of a given pig herd and provides the basis for reliable production of animal goods.…”
Section: Discussionmentioning
confidence: 99%
“…One crucial pillar of disease control is the genetic characterization of circulating virus strains in order to identify the origin of infection and determine the routes of transmission between pig farms, within a geographical region or an administrative area. Sequencing one of the most variable genomic regions, the ORF5, is still a gold-standard procedure for surveying these issues [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. The information obtained by means of molecular epidemiology further assists the improvement of external disease control measures of a given pig herd and provides the basis for reliable production of animal goods.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the e cacy of PRRSV vaccines in China has signi cantly weakened, and new infection cases have been reported in multiple regions. The main reason for this lies in the fact that PRRSV, being an RNA virus, lacks proofreading mechanisms during its replication, making it highly prone to mutations, resulting in diverse and complex patterns of its prevalence [9,49]. Similarly, porcine circovirus, especially PCV2, exhibits a high genetic variability despite being a DNA virus, with nucleotide mutation rates comparable to RNA viruses.…”
Section: Discussionmentioning
confidence: 99%
“…Because the response to infection might vary by individual, these results might not represent animals born to subsequent weekly batches. In fact, this could be illustrated by a recent study in which higher PRRSV1 diversity was found within batches 1.5 months after the outbreak onset than within batches 12 months after, possibly representing the emergence of an escape variant [ 38 ].…”
Section: Discussionmentioning
confidence: 99%